Systèmes de politique de l’emploi et de protection sociale en France et en Grande-Bretagne : un consensus sur l’offre de travail ? - Christine Erhel; Hélène Zajdela (Revue Française de Civilisation Britannique)
In the field of the comparative analysis of social protection, existing debates show a growing interest for the links between social protection institutions and benefits on the one hand, and labour market policies on the other (including labour market regulations, like minimum wages, working time, short-term contract rules, etc.). From this point of view, a comparison between the French case and the British case seems interesting and stimulating. Indeed, as far as fundamental principles of social protection and national labour market policy models are concerned, these two countries are rather opposed at the beginning of the 1990s, but the end of the 1990s and the beginning of the 2000s exhibit converging reforms. In this article, we focus on the dynamics and reforms of social protection and labour market policy systems during the 1990s, in France and in the United Kingdom. We show that the United Kingdom and France remain on differentiated institutional paths, corresponding to the typology of traditional social protection models. Nevertheless, some converging evolutions and reforms are found at the end of the period.